Rand protease: the role of calcium-binding site on stability with mutagenesis and the effectiveness on leather dehairing - Phang, Zi Wei; Nur Aliyah Mohd Azrin,; Mohd Shukuri Mohamad Ali,; Noor Dina Muhd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bacillus subtilis produces a number of proteases, which are highly demanded in various industries, especially the thermostable one. Rand protease, originally isolated from B. subtilis, has thermostability and other remarkable properties such as organic solvent tolerance and pH stability. However, its vulnerability to instability-induced degradation has limited its applications. Because Rand protease contains two calcium ions for folding, activation, and, above all, stability, previous studies have shown that boosting the calcium-binding affinity enhances stability. Therefore, Rand protease’s susceptibility to degradation could be remedied by discovering the calcium-binding site having the greatest impact on stability for further calcium-binding affinity improvement. This was done with an in silico mutagenesis approach whereby one calcium-binding site was mutated to alanine and evaluated either the RMSD, the deviation of the mutated configuration from the original configuration using YASARA, or stability in terms of kcal/mol using HotSpot Wizard. The result found that calcium-binding sites Leu75 from YASARA and Tyr171 from HotSpot Wizard have higher influences on stability (our target). This result was also validated using Pymol, ExPASy ProtParam, and Molprobity. Additionally, Rand protease-chemical formulation dehairs leather best without additional metal ions at pH 7.0 and for 18 h. It also produced higher-quality leather with smaller pores and softer leather than chemical formulations. In contrast, hair breakage was observed in calcium treatment, which is compatible with the low dehairing activity achieved. In conclusion, Leu75 and Tyr171 are vital for calcium stabilisation and this enzyme has demonstrated its crucial efficacy in the leather dehairing industry.